Quality of life of treated opiate addicts in the methadone maintenance program and those treated with buprenorphine - Marinković, Mirjana; Djordjević-Jovanović, Lidija; Miljković, Snežana; Milojković, Bobana; Janjić, Vladimir (Vojnosanitetski pregled, 2017)
Background/Aim. Although the characteristics of the treatment are the most researched determinants of quality of life of opiate addicts, it is indisputable that there is a certain influence of the characteristics of addicts and addiction, too. The aim of this study was to determine which addicts characteristics, as well as the characteristics of the addiction and treatment have predicative influence on the quality of life of the opiate addicts treated in the methadone maintenance program and those treated with buprenorphine. Methods. The epidemiological cross-sectional study was carried out in 2013 at the Clinical Center Niš, on a total of 64 opiate addicts, both sexes, aged 18 and older (32 addicts in the methadone program, chosen by random selection, and 32 addicts treated with buprenorphine, matched by sex and age). Necessary data were collected in a “face to face” interview with the examinees, based on the autonomous kind of a questionnaire, together with the use of the standardized World Health Organization (WHO) instruments: for health status, for the level of severity of addiction and for the quality of life measuring) based on which the health index (EQ-5D), Addiction Severity Index (ASI) and the quality of life index (WHOQOL-BREF) were calculated. The data were described by the methods of descriptive statistics, while the differences between groups were analyzed by applying χ2 and t-test. Multiple regressions were used to determine the predictors. Results. The addicts in the methadone program showed much worse perception of quality of life than those treated in another way, although, according to the values of quality of life, they did not differ significantly. The most numerous predictors of the level of quality of life were health characteristics, characteristics of the socioeconomic position of the examinees, as well as different consequences of addiction. The influence of treatment was less noticeable. Participating in the methadone program had predicative influence on perception and the level of quality of life of the addicts in mental area and that of the environment. The influence of the characteristics of methadone treatment in physical and social area was insignificant. Conclusion. Variations in the perception and level of the quality of life of opiate addicts in different areas cannot be explained using only one predictor. The number of determining variables is large, and its impact complex.